5 - Limite des alternatives capitalistes d'état ou privées a la crise agricole africaine - Bernard FOUNOU-TCHUIGOUA, (Africa Development, 1985)
Basing his analysis on the BERG Report, the author is considerin in this article the merits of respectively public enterprises and private one as a strategy for agricultural revolution in a West-African country wit trovert economy. From the point of view of the World Bank, it is the intervention of the state at the micro-economic level resulting in the expansion of the public enterprise which is one of the causes of the socio-economic crisis Africa is facing. Hence the recommendation of the World Bank that state should rather use macro-economic political instruments as well as favour private enterprise. Then the author defines what he means by agricultural revolution before describing how the transition to this revolution should be condu He also shows the limitations of the private sector namely the reductance and difficulties of international and national private capital to invest in agricultural production. The author expresses serious doubts as to existence or even the role of a genuine public sector within the contex a dependent economy. The writer is of the opinion that neither the public sector nor t private one can lead to agricultural revolution in West Africa. The issue of the choice between private agrarian capitalism and state agrarian capitalism is only pertinent within the framework of self-centred development.